2012
DOI: 10.2174/1874192401206010015
|View full text |Cite
|
Sign up to set email alerts
|

Gender and Socio-economic Differences in Daily Smoking and Smoking Cessation Among Adult Residents in a Greek Rural Area

Abstract: Despite the well-known health risks, smoking is still highly prevalent worldwide. Greece has the highest level of adult smoking rate (40%) across the European Union. We investigated gender and socio-economic differences in daily smoking and smoking cessation among Greek adults. We conducted a cross-sectional survey between October and November 2009 in 434 adults residing in a Greek rural area. Data were collected with the use of the World Health Organization Global Adult Tobacco Survey (WHO GATS) Core Question… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…This is a concern because, as foreshadowed, the risks from smoking are even greater for females than males and the dangers of relapse post-diagnosis or hospitalization for CHD are significant in terms of subsequent mortality and morbidity in both genders. 8,19,25,36,42 In this meta-analysis, the rate of persistent smoking or relapse post-diagnosis or hospitalization was similar amongst females and males. This is contrary to our hypothesis which suggested that females might find it more difficult to quit smoking than males and, therefore, be more vulnerable to relapse.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…This is a concern because, as foreshadowed, the risks from smoking are even greater for females than males and the dangers of relapse post-diagnosis or hospitalization for CHD are significant in terms of subsequent mortality and morbidity in both genders. 8,19,25,36,42 In this meta-analysis, the rate of persistent smoking or relapse post-diagnosis or hospitalization was similar amongst females and males. This is contrary to our hypothesis which suggested that females might find it more difficult to quit smoking than males and, therefore, be more vulnerable to relapse.…”
Section: Discussionmentioning
confidence: 76%
“…20,52 Whilst gender does not, therefore, appear to be a predictor for relapse, factors which have been found to be associated with failed quit attempts or resumption postdischarge include: low-confidence in quitting; fewer prior attempts to quit; low household income; having other smokers in the household; high nicotine dependence; low self-efficacy; severity of withdrawal symptoms; lower education level; ethnicity; behavioral and psychosocial factors. 14,16,19,[53][54][55] People who are depressed or suffer from anxiety or psychiatric disorders are known to be particularly vulnerable to relapse. 14,50 Women have been shown to find smoking cessation more difficult at certain stages of the menstrual cycle; but in light of the older age of onset of CHD in women, 6 it is unlikely to be a factor in smoking relapse amongst this generally post-menopausal cohort.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In many Western countries, the prevalence of smoking among men and women is roughly similar (Birmpili et al, 2012; Croghan et al, 2009). In Taiwan, men have a much higher prevalence of smoking (39.0%) as compared to women (5.1%; Chang, Sung, Zhu, & Chiou, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown that race can influence the APOE genotype's effect on cognition (28–30). Finally, we had sex differences in the normal cognition group versus the mild cognitive impairment group, and sex differences are known to influence smoking outcomes (3133). …”
Section: Discussionmentioning
confidence: 99%